2022
DOI: 10.3390/land11122335
|View full text |Cite
|
Sign up to set email alerts
|

Harms to Community Food Security Resulting from Gender-Based Violence

Abstract: While the right to food and community self-reliance underpin current knowledge and interpretation of community food security (CFS), the literature on CFS seldom accounts for the ways in which gender-based violence (GBV) disrupts and undermines CFS. In this review, we make the case that GBV in CFS contexts manifests as a continuum, involving different forms of violence that blend into and reinforce each other, fueling social degradation and undermining the capacity of community food system workers to prioritise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The hurricanes also impeded public health efforts by damaging hospital infrastructure including potable water and cold chain equipment for vaccines ( PAHO and WHO, 2022 ). Gender-based violence, which affects household food security ( Okpara and Anugwa, 2022 ), can be impacted by changing social and economic dynamics within households as a result of both climate change ( Caridade et al, 2022 ) and the COVID-19 pandemic (Chandan et al, 2020); Honduras saw a 14% increase in reports of gender-based violence between February and May 2022 ( Fromm et al, 2022 ). Scholars have described “the three Cs” as “uneven crises” with compounding, inequitable impacts on vulnerable populations including women, lower-income households, racially/ethnically marginalized groups, and communities in climate hotspots ( Belsey-Priebe et al, 2021 ; Sultana, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hurricanes also impeded public health efforts by damaging hospital infrastructure including potable water and cold chain equipment for vaccines ( PAHO and WHO, 2022 ). Gender-based violence, which affects household food security ( Okpara and Anugwa, 2022 ), can be impacted by changing social and economic dynamics within households as a result of both climate change ( Caridade et al, 2022 ) and the COVID-19 pandemic (Chandan et al, 2020); Honduras saw a 14% increase in reports of gender-based violence between February and May 2022 ( Fromm et al, 2022 ). Scholars have described “the three Cs” as “uneven crises” with compounding, inequitable impacts on vulnerable populations including women, lower-income households, racially/ethnically marginalized groups, and communities in climate hotspots ( Belsey-Priebe et al, 2021 ; Sultana, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies has shown that most have concentrated on the ability to minimise or decrease GBV, especially domestic violence, with fewer studies focused on the role of economic empowerment and emotional violence (Bhana et al 2021;Eger 2021;Nunbogu and Elliott 2022;Montserrat et al 2022;del Mar Rodas-Zuleta et al 2022;Freijomil-Vázquez et al 2022). Another strand of studies focused on the micro-level (Bashford-Squires et al 2022;Tsai 2022;Okpara and Anugwa 2022;Mcilongo and Strydom 2021), while other studies carried out systematic reviews (Keith et al 2022;Sabri et al 2022; van Daalen et al 2022;Villardón-Gallego et al 2023;Mbukanma and Strydom 2021). Further studies concentrated on health, music, and socioeconomic issues such as sexuality, water, sanitation, and hygiene (Nunbogu and Elliott 2022;Philbrick et al 2022;Zhou et al 2022;Mahamid et al 2022;Raftery et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women producers frequently lack access to education and training opportunities, which can hinder their ability to adopt new technologies and practices to improve productivity and profitability [ 27 ]. Additionally, women may face discrimination and harassment in their work, as well as limited access to markets and other economic opportunities [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there are some programs and strategies that have been implemented to address GBV in agricultural settings, such as microfinance programs, advocacy for equal land rights and the promotion of gender-sensitive training [ 25 , 29 ], GBV remains an under-recognised reality, compounding the existing challenges faced by women producers in LMICs. As noted by Okpara and Anugwa, “GBV is not only a human rights violation, but also a catalyst to social degradation and food insecurity” [ 28 ] (p.12). The significance of addressing GBV, particularly in the context of women producers in LMICs, cannot be overstated.…”
Section: Introductionmentioning
confidence: 99%